On the Group C^*-Algebras of a Semidirect Product of Commutative and Finite Groups - Samoilenko, Yu. S.; Yushchenko, K. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
By using representations of general position and their properties, we give the description of group C^*-algebras for semidirect products Z^d × G_f, where G_f is a finite group, in terms of algebras of continuous matrix-functions defined on some compact set with boundary conditions. We present examples of the C^*-algebras of affine Coxeter groups.